2020
DOI: 10.12729/jbtr.2020.21.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Melia azedarach extract exhibits a broad spectrum of antiviral effect in vitro and in vivo

Abstract: Melia azedarach is commonly used in traditional and folk medicine in Korea and China to treat a variety of diseases including diarrheal, diabetic, rheumatic, and hypertensive disease. The aim of this study was to determine the potential prophylactic and therapeutic effects of Melia azedarach against a broad spectrum of viruses in in vitro cell culture model and the protective effect against different influenza A subtypes in BALB/c mice model. An effective dose of pre-treatment, co-treatment, and post-treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The tree Melia azedarach (Family: Meliaceae) is locally recognized as a bakain or drek (Hindi), Persian lilac or China tree (English), and Fleurs lilas (French). In South America, it is generally known as “paraiso” or paradise, and in the US as the Indian lilac or white cedar [ 16 ]. The whole plant or its specific parts (leaves, stems, and roots) are known to have medicinal properties and an extended history of use by indigenous and tribal people in India.…”
Section: Discussionmentioning
confidence: 99%
“…The tree Melia azedarach (Family: Meliaceae) is locally recognized as a bakain or drek (Hindi), Persian lilac or China tree (English), and Fleurs lilas (French). In South America, it is generally known as “paraiso” or paradise, and in the US as the Indian lilac or white cedar [ 16 ]. The whole plant or its specific parts (leaves, stems, and roots) are known to have medicinal properties and an extended history of use by indigenous and tribal people in India.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we explored the in vitro viral inhibitory activity of M. azedarach L. leaves extract against SARS-CoV-2 which is so far not studied. Nethmini et al found that M. azedarach L. could turn off the replication of herpes simplex virus, coxsackie virus, enterovirus, influenza A virus, and bovine rhinovirus in both epithelial and macrophage cell lines [46].…”
Section: Plos Onementioning
confidence: 99%
“…Melia species can grow rapidly, and they are widely grown in China, especially M. azedarach , because of the mechanical properties of their wood, which makes them resistant to insects, pathogens, and corrosion [ 1 ]. Melia species are also often used as medicinal plants for the treatment of various diseases, including diarrhea, diabetes, rheumatic diseases, and hypertension [ 5 ]. Several studies have examined the chemical constituents (e.g., limonoids and triterpenoids) extracted from the fruits, stem bark, and leaves of M. azedarach and M. toosendan [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%